Characterization of water-insoluble oxidative potential of PM2.5 using the dithiothreitol assay. (1st March 2020) - Gao, Dong; Mulholland, James A.; Russell, Armistead G.; Weber, Rodney J.
Abstract: Both water-soluble and insoluble components of ambient particulate matter (PM) have been shown to contribute to the oxidative potential (OP) of PM. In this study, we used the dithiothreitol (DTT) assay to assess the water-soluble (OP WS−DTT ) and total OP (OP total−DTT ) of ambient fine particles (PM2.5 ), with water-insoluble OP (OP WI−DTT ) determined by difference. Ambient PM2.5 filter samples were collected daily during 2017 in urban Atlanta and were analyzed for OP and major PM components. Results from measurements suggested a measurable contribution of water-insoluble components to OP DTT, which comprised on average 20% of total PM OP. Strong seasonal trends were observed in both volume- and mass-normalized OP total−DTT and OP WI−DTT, with higher values in the winter than in the summer, possibly driven by biomass burning emission seasonality. Correlation analysis indicated that all forms of OP DTT measurements were related to organic species and metals. OP total−DTT and OP WI−DTT were correlated with brown carbon (BrC) and total metals, especially total crustal elements. A multivariate regression model was developed for OP total−DTT based on particle composition data. The model suggested that the variability of OP total−DTT was primarily affected by BrC, followed by EC, total Cu and an antagonistic interaction between BrC and total Cu. Highlights: Water-insoluble PM species contributed 20% of PM2.5 oxidative potential (OP). Seasonal trends of water-insoluble and total OP were discernible: winter > summer. Variability in total OP was primarily driven by brown carbon (BrC). Water-insoluble OP was associated with BrC and total metals.